A Synthesis of the Literature on Trauma-Informed Care. (2nd September 2015) - Reeves, Elizabeth
Abstract : Patients with a history of traumatic life events can become distressed or re-traumatized as the result of healthcare experiences. These patients can benefit from trauma-informed care that is sensitive to their unique needs. However, despite the widespread prevalence of traumatic life experiences such as sexual assault and intimate partner violence, trauma-informed care has not been widely researched or implemented. The purpose of this synthesis of the literature is to examine existing research on trauma-informed care for survivors of physical and sexual abuse. The following themes are discussed: trauma screening and patient disclosure, provider-patient relationships, minimizing distress and maximizing autonomy, multidisciplinary collaboration and referrals, and trauma-informed care in diverse settings. This synthesis also explores implications for trauma-informed care research, practice and policy. The themes identified here could be used as a framework for creating provider and survivor educational interventions and for implementing trauma-informed care across disciplines. The findings of this synthesis support further research on patient and provider experiences of trauma-informed care, and research to test the efficacy of trauma-informed care interventions across healthcare settings. Universal implementation of trauma-informed care can ensure that the unique needs of trauma survivors as patients are met, and mitigate barriers to care and health disparities experienced by this vulnerable population.